Peran Hukum Pidana Internasional dalam Penanggulangan Tindak Pidana Terorisme - Fatimah Azzahra; Mawar Sapanah; Dean Putri Amelia; Selvi Tetrya (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Terrorism is a form of international crime that poses a serious threat to global security and peace, which can have an impact that violates fundamental human rights. Terrorism is characterized by its transnational, organized nature and cross-border networks, which necessitates a well-coordinated international legal response at both the national and international levels. This study aims to determine and analyze how the principles of international criminal law are applied in combating terrorism and to identify the challenges of harmonizing national law with international law in combating transnational terrorism. The research method used is normative juridical. The results of the study show that the application of international criminal law principles, including universal jurisdiction and the role of the International Criminal Court (ICC), is important in ensuring that perpetrators of terrorism do not escape legal responsibility. However, in harmonizing national law with international law, there are still differences in the definition of terrorism, legal systems, and state sovereignty.